Evaluation of Prescription Pattern of Antibiotic for Surgical Prophylaxis Use in a Tertiary Care Hospital - Vigneswaran, R; Cresenciya, J Renita; Jeevithalakshmi, P; Sakthisuvetha, RV; Senthilkumar, SR (Indian Journal of Pharmacy Practice)
Objectives: The aim of this study was to evaluate the utilization pattern of antibiotics for surgical prophylaxis in patients undergone surgery at Government District Headquarters Hospital, Virudhunagar. Materials and Methods: This study was conducted for 6months (May- October 2021). Patients who were more than 18 years of age admitted in general surgical, orthopedic and gynecology wards receiving at least one dose of any class of antibiotics orally or intravenously were included in this study. Results: A total of 180 patients were undergoing post operative care during the study period in surgery ward of Government Headquarters Hospital, Virudhunagar. Among 180 patients 34% (62) patients were aged between 31 to 45, 32% (58) patients were aged between 46-60, 18% (32) patients were aged between 18-30, 13% (24) patients were between 61-75, 2% (4) patients were aged between 76-90. Conclusion: Reduction of surgical site infections decreases the post-operative morbidity, mortality rate. Combination therapy of antibiotic use gives more success in treat infection when compared with monotherapy use of antibiotics.
Keywords: Surgical site infection; Antibiotics; Surgical prophylaxis; Cefotaxime